Development of a Web-Based Liturgical Presentation System with Quick Switch and QR Code Using R&D Method - Juan Sebastian Sijron Lahope; Benny Pinontoan; Wisard Kalengkongan; Mahardika Inra Takaendengan; Eliasta Ketaren; Edwin Tenda (Journal of Artificial Intelligence and Technology Information (JAITI), 2026)
Church worship services require a system that can assist in organizing and presenting worship materials in a structured manner so that congregants can follow the service effectively. However, the conventional presentation of liturgy, Bible verses, and songs creates challenges in material management, slide transition flexibility, and limited access for congregants. This study aims to design and implement a web-based liturgical presentation system to improve efficiency and flexibility in managing and delivering worship materials in a single church, namely GMIM Kanaan Likupang Dua. The research employs the Research and Development (R&D) method, which includes requirement analysis, system design using Unified Modeling Language (UML), development, testing, and evaluation. The system is developed using PHP with the Yii Framework 2 and MySQL database, implementing the Model-View-Controller (MVC) architecture. The main features include liturgy management, web-based presentation, a Quick Switch feature for rapid content changes, and QR Code integration that enables congregants to access presentation content through personal devices. Black Box Testing results indicate that all system functions operate properly. Furthermore, User Acceptance Testing (UAT) shows a high level of user acceptance, with 98.75% from multimedia staff and 88.86% from congregants. Therefore, the developed system is considered feasible and effective in supporting more structured, responsive, and inclusive worship services.